MANAJEMEN PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN HASIL BELAJAR IPASâ€ (STUDI KASUS KELAS V SD NEGERI PUSAKASARI) - Lia Sri Mulyati (Indonesian Journal of Elementary Education (IJOEE), 2025)
AbstractThis research describes how Project-Based Learning (PjBL) management can be implemented to enhance Science, Social Studies, and Natural Sciences (IPAS) learning outcomes for fifth-grade students at SD Negeri Pusakasari. The study's background stems from the initial condition of low IPAS learning achievements and limited student engagement in the learning process, largely due to traditional teaching methods. PjBL was proposed as an innovative solution given its potential to encourage active participation, critical thinking, and collaborative skills among students. The research employed a qualitative approach with a case study method, collecting data through observation, in-depth interviews, and document analysis. The gathered data were analyzed descriptively. The findings indicate that PjBL implementation was carried out through four key managerial stages in accordance with Daft's theory: planning, organizing, leading, and controlling. Each stage was applied systematically and adapted to the students' needs and the Merdeka Curriculum. This PjBL management successfully improved students' IPAS learning outcomes across cognitive, affective, and psychomotor aspects. Nevertheless, challenges were identified, such as limited facilities and students' ability to use digital media. To address these, strategies were proposed, including optimizing school assets and providing intensive mentorship. Theoretically, this research contributes to the literature on innovative learning management. This study offers a replicable PjBL managerial model for other primary schools with similar characteristics.Keywords: project-based learning, learning management, student learning outcomes, IPAS